Kemampuan Komunikasi Matematis Peserta Didik yang Diajar dengan Metode Probing-Prompting Learning Pada Kelas Vii Mtsn Bungus Teluk Kabung Padang Tahun Ajaran 2017/2018 - Nelwati, Sasmi; Yeni, Yelpa (Universitas Islam Negeri Imam Bonjol Padang, 2019)
Communication ability of mathematic is one of purpose in learning that hoped can developed in mathematic learning. Base on observation result in MTsN Bungus Teluk Kabung Padang show that communication ability of mathematic student still low. The purpose of this research is to know about students ability on mathematics communication at grade VII MTsN Bungus Teluk Kabung Padang academic year 2017/2018 that taught by Probing-Prompting Learning Method. This type of research is quasi experimental (Quasi Experimental Research) with Randomized Control Group Only Design. Population in this research is student in grade VII MTsN Bungus Teluk Kabung Padang academic year 2017/2018. Data collection method use are posttest obtained is analyzed by using t – test after normality test and homogenity test. Based on the research result, mathematical communication ability of experment class student is higher than control class.After doing analysis, the average score of the experiment class is 80,00 while the control class is 73,42. After hypothesis testing using t-test, obtained tcount > ttable (1,82> 1,66) with α = 0,05 on the level trust is 95%, then the decision is H0 rejected and H1 accepted.